Market information: Computerizing dairy cooperatives - Kiplagat, Rop (Technical Centre for Agricultural and Rural Cooperation, 2009)
Faced with increased competition and fewer subsidies, many Kenyan dairy cooperatives are now using an information management program specially developed to help them operate more efficiently.